2012
DOI: 10.1177/0886260512441253
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Domestic Violence

Abstract: Researchers in this study examined the attitudes toward domestic violence, the victim, and her perpetrator. A total of 194 participants were randomly assigned to one of 4 hypothetical scenarios to evaluate how observers' perceptions were influenced by their own sex and myths about domestic violence, by the victim's decision to return to the abusive relationship, and by the relationship status of the victim (dating or married to the perpetrator). Results demonstrated significant main effects of participant's se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 36 publications
(37 reference statements)
7
65
0
10
Order By: Relevance
“…34, nº 1 (january) Cantera & Blanch, 2010;Valor-Segura et al, 2011). A vast number of studies have revealed that people with traditional beliefs about gender roles are more likely to endorse justifications of IPV than people with egalitarian beliefs (e.g., Yamawaki, Ochoa-Shipp, Pulsipher, Harlos, & Swindler, 2012). Regarding sexist beliefs, hostile sexism (legitimisation of violence against women challenging the power of men) supports the justification of IPV, victim blaming and exonerating perpetrators (Glick, Sakalli-Ugurlu, Ferreira, & de Souza, 2002;Sakalli, 2001).…”
Section: Attitudes To and Beliefs About Ipvmentioning
confidence: 99%
“…34, nº 1 (january) Cantera & Blanch, 2010;Valor-Segura et al, 2011). A vast number of studies have revealed that people with traditional beliefs about gender roles are more likely to endorse justifications of IPV than people with egalitarian beliefs (e.g., Yamawaki, Ochoa-Shipp, Pulsipher, Harlos, & Swindler, 2012). Regarding sexist beliefs, hostile sexism (legitimisation of violence against women challenging the power of men) supports the justification of IPV, victim blaming and exonerating perpetrators (Glick, Sakalli-Ugurlu, Ferreira, & de Souza, 2002;Sakalli, 2001).…”
Section: Attitudes To and Beliefs About Ipvmentioning
confidence: 99%
“…(Sarkar, 2008;Yamawaki et al, 2012) or questions which ask what are the barriers to healthcare professionals undertaking enquiry about DVA? (Baig et al, 2012;Jenner et al, 2015;Rose et al, 2011;Sprague et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…College students have exhibited lower willingness to report in response to vignettes with intimate partner conflict, fewer concerning behaviors, and no threatening verbalizations (Hollister et al, 2014;Tarling & Morris, 2010;Weller et al, 2013;Yamawaki et al, 2012). College students most willing to report in response to vignettes have had greater campus connectedness and trust in campus authorities.…”
mentioning
confidence: 91%
“…Studies utilizing vignettes of concerning behavior within college student samples have further clarified incident-related and attitudinal influences (Hollister et al, 2014;Sulkowski, 2011;Weller et al, 2013;Yamawaki et al, 2012), but may have limited applicability to actual reporting decisions (Baumeister, Vohs, & Funder, 2007;Shaffer, Peller, Laplante, Nelson & Labrie, 2010). College students have exhibited lower willingness to report in response to vignettes with intimate partner conflict, fewer concerning behaviors, and no threatening verbalizations (Hollister et al, 2014;Tarling & Morris, 2010;Weller et al, 2013;Yamawaki et al, 2012).…”
mentioning
confidence: 94%
See 1 more Smart Citation